PENERAPAN PENDEKATAN SAINTIFIK PADA ASPEK PENILAIAN DALAM PEMBELAJARAN TEKS NEGOSIASI DI KELAS X SMK MUHAMMADIYAH 1 PADANG - Elvianto, Suci; Nursaid, Nursaid; Zulfikarni, Zulfikarni (Universitas Negeri Padang, 2018)
This study aims to describe the application of scientific approach on the aspect of assessment in learning the text of the negotiation in class X SMK Muhammadiyahh 1 Padang. This study used descriptive qualitative method. The results of the study show the learning appraisal tool used by the teacher, ie practice/performance assessment, observation, project and investigation assessment, journal assessment, diary, open response questions, and portfolio. Learning learning activities are conducted through observing, questioning, trying, and communicating activities. Assessment of the teacher, namely penilian on aspects of attitude, knowledge and skills.Kata kunci: proses pembelajaran, teks negosiasi, saintifik